Tindak Tutur Representatif pada Video Konsep Dasar Memahami Manusia dalam Platform YouTube Cania Citta - Aprillia Puspita Sari; Khairunnisa Ardhana; Fadla Cahya Salsabila; Intan Puspita Listyani; Sisya Nirmala Meida; Tiara Dihas Sapuri; Asep Purwo Yudi Utomo (Universitas Palan, 2026)
This research aims to describe the forms and functions of representative speech acts found in the YouTube video “The Basic Concept of Understanding Humans” by Cania Citta. The study arises from the phenomenon of digital communication, which demonstrates a shift in speech patterns from merely delivering information to constructing intellectual discourse that is both reflective and argumentative. A descriptive qualitative method with a pragmatic approach was employed. The data, consisting of representative utterances, were collected through observation and note-taking techniques on video transcripts, then analyzed using Miles and Huberman’s interactive model, which involves data reduction, data presentation, and conclusion drawing. The findings reveal that the dominant representative speech acts include stating, explaining, reporting, concluding, and speculating. Each utterance functions not only to convey information but also to build rational argumentation and foster critical awareness among audiences regarding the concept of humanity. Illocutionarily, these utterances perform informative, argumentative, and reflective functions, emphasizing the speaker’s epistemic responsibility toward the truth of the propositions delivered. The perlocutionary effects include an increased interest and heightened critical awareness among audiences concerning philosophical issues about human nature. This study contributes to the development of pragmatic studies, particularly in understanding the role of language as an instrument of knowledge and persuasion in digital media.